MANAJEMEN STRATEGI DINAS PERDAGANGAN, KOPERASI DAN USAHA MIKRO DALAM UPAYA MENJAGA STABILITAS HARGA BERAS - Nur Fa'izah; Ahmad Suprastiyo; Cahya Lukita (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This research aims to investigate the strategic management implemented by the Department of Trade, Cooperatives, and Micro Enterprises in Bojonegoro Regency in maintaining the stability of rice prices. This is due to the inflation of rice prices, which are above the highest retail price. The research method is qualitative with a descriptive approach. Informant identification is carried out through Nonprobability Sampling Technique using purposive sampling method. Data collection techniques involve interviews and observations. This study refers to the theory of strategic management according to Freed R. David, focusing on Strategy Formulation, Strategy Implementation, and Strategy Evaluation. The research findings indicate that the strategic management undertaken by the Department of Trade, Cooperatives, and Micro Enterprises to maintain the stability of rice prices involves market operations and affordable markets, which are implemented in accordance with applicable regulations. However, there are still cases where some traders sell at prices that have been set. The conclusion drawn is that the strategic management carried out by the Department of Trade is functioning well, but increased field supervision is still needed to ensure the effectiveness of these strategies.